2019
DOI: 10.1161/circimaging.119.008905
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cutoff Value of Fractional Flow Reserve Derived From Coronary Computed Tomography Angiography for Predicting Hemodynamically Significant Coronary Artery Disease

Abstract: Background: The optimal cutoff value of fractional flow reserve (FFR) derived from coronary computed tomography angiography (FFR CT ) remains unclear. Methods: The current study population consisted of 93 patients with 139 vessels, who had suspected coronary artery disease by computed tomography angiography and underwent invasive FFR. We evaluated diagnostic performance of FFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Therefore, reconsideration of the measurement site for FFR CT in the present study may lead to improved diagnostic accuracy of FFR CT analysis, especially specificity and PPV. It has also been reported that reconsideration of the cut-off value of FFR CT may improve diagnostic accuracy, 19 and future large-scale studies that consider reconsideration of the measurement site or cut-off value are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reconsideration of the measurement site for FFR CT in the present study may lead to improved diagnostic accuracy of FFR CT analysis, especially specificity and PPV. It has also been reported that reconsideration of the cut-off value of FFR CT may improve diagnostic accuracy, 19 and future large-scale studies that consider reconsideration of the measurement site or cut-off value are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…It is a definite value rather than a range. The discrimination of ischemia by CT-FFR is more likely to be correct when the difference between real FFR value and the threshold of ischemia (FFR ≤ 0.8) is large ( 26 ). On the contrary, the dichotomous diagnosis is prone to be error when actual FFR is close to 0.8, even with a slight deviation of CT-FFR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…51 Other researchers have suggested that the "gray zone" of CT-FFR should be set between 0.70 and 0.80 to improve the positive predictive value of CT-FFR. 59,60 Regardless, for patients whose CT-FFR value is in the "gray zone," more factors need to be considered to determine if revascularization is appropriate. These factors include the symptoms (especially the severity of chest pain), risk factors, the area of blood supply to the myocardium, and the results of functional testing, such as myocardial perfusion imaging, to provide the patients with the safest and most appropriate treatment (Fig.…”
Section: Interpretation Of Ct-ffrmentioning
confidence: 99%
“…Therefore, some scholars believe that a cutoff value of 0.75 may be more appropriate for detecting hemodynamically significant ischemia because it has higher specificity (78%) and acceptable sensitivity (86%) than the threshold of 0.80 51. Other researchers have suggested that the “gray zone” of CT-FFR should be set between 0.70 and 0.80 to improve the positive predictive value of CT-FFR 59,60. Regardless, for patients whose CT-FFR value is in the “gray zone,” more factors need to be considered to determine if revascularization is appropriate.…”
Section: Interpretation Of Ct-ffrmentioning
confidence: 99%